Environmental Load Variations for the Three Malaysian Offshore Regions - George Mathew, Theodora Thomas (Universiti Teknologi PETRONAS, 2018)
Environmental loads are the drivers on the design of jacket offshore platforms which are installed in shallow waters for the exploration and extraction of oil and gas. There are two main environmental loads considered in this study which are the wave and current loads. This study focused on the variations of design parameters, Hmax and Tass acting on the 75 meters depth of jackets located at the three Malaysian waters namely Peninsular Malaysian Operations (PMO), Baram Delta and Samarang. The study was made in such a way that they could represent all of the offshore regions of Malaysia which belongs to Sabah, Sarawak and Peninsular Malaysia. The jacket members consist of slender cylinders with tubular cross section.